Penguatan Moderasi Beragama Masyarakat melalui Revitalisasi Buku Ratibul Haddad di Desa Kedungrejo - Imam Fahrurrozi; Budi Sufyanto; Zainal Arifin (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This community service initiative aims to strengthen religious moderation through the revitalization of reciting Ratibul Haddad among young Islamic students (santri) at the Kedungrejo Village Musholla in Muncar District. The method employed is Participatory Action Research (PAR), integrated with an Asset-Based Community Development (ABCD) approach, to optimize existing local spiritual assets such as the ratiban tradition and the Nahdlatul Ulama institutional framework. The program involved 28 santri in a series of activities, ranging from participatory observation, collaborative planning, regular mentoring, to evaluative reflection. The results indicate significant improvement in three key aspects: (1) Cognitive-Spiritual, reflected in enhanced reading ability and comprehension of the meanings within Ratibul Haddad; (2) Affective-Emotional, characterized by the growth of inner peace, discipline, and religious enthusiasm; and (3) Social-Communal, marked by strengthened group cohesion and the musholla's enhanced role as a central hub for mentorship. This activity successfully instilled a new, sustainable habit, supported by the establishment of peer educators and the commitment of the musholla's management. It is concluded that a participatory approach based on local assets is effective not only for transferring religious knowledge but also as a concrete strategy in building the foundations of religious moderation and the religious character of the younger generation from an early age.